1987
DOI: 10.1007/bf00377917
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of personal exposure to ambient nicotine in daily environment

Abstract: To evaluate the actual exposure level of nonsmokers to environmental tobacco smoke (ETS) in their daily life, the exposure level of ambient nicotine was measured with a nicotine personal monitor carried by a nonsmoker. Average exposure levels of nicotine, even in such smoky places as cars, coffee shops and pubs, were less than 45 micrograms/m3. As a result of all-day monitoring, the highest amount of nicotine inhaled in a day was estimated, in this study, to be up to 310 micrograms, equivalent to actively smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The measured nicotine con centrations (table 1-3) from a few to 90 pg/m3 are of the same order of magnitude as those reported in other stud ies [5,[10][11][12],…”
Section: Additional Locationssupporting
confidence: 74%
“…The measured nicotine con centrations (table 1-3) from a few to 90 pg/m3 are of the same order of magnitude as those reported in other stud ies [5,[10][11][12],…”
Section: Additional Locationssupporting
confidence: 74%
“…The children reached significantly higher U-cotinine,, than the adults (means: 22 [95% confidence interval (95% CI), 18-261 versus 13 [95' /0 CI, 9.0-1 61 mg/l adj, p = .005 [Table 11). Furthermore, the mean U-cotinine at the plateau, which was correlated closely to the Ucoti ni ne,,, (R2 = .94) was significantly higher in children than in adults (1 8 versus l l mg/l adj; p = .002).…”
Section: Resultsmentioning
confidence: 96%
“…Means of 3.1-4.5 mg/m 3 (Moschandreas and Vuilleumier, 1999) and 6.0 mg/m 3 (Maskarinec et al, 2000) were reported in smoking sections of US restaurants. Mean nicotine levels of 14.8 mg/m 3 (Muramatsu et al, 1987) (Meger et al, 2000), and 0.4-46 mg/m 3 averaged at 7.0 mg/m 3 (Hyva¨rinen et al, 2000) have been published. Nicotine levels shown in Table 2 are within the range of previously reported results in the comparable geographic regions.…”
Section: Nicotine Resultsmentioning
confidence: 99%